András Visky's Barrack Dramaturgy : memories of the body - Visky, András, 1957- (Playtext series., 2017)
This volume is a collection of plays created by András Visky, one of the most innovative voices in Hungarian theatre. Translated for English-language audiences, the book provides critical analyses, scripts, director's notes and interviews with creative teams behind the productions to reveal a holistic, insider's view of Visky's artistic vision.